Production and characterization of gum exudate from apricot tree: modeling the rheology of the obtained extract - Karatas, Mukaddes; Aydogmus, Ercan; Arslanoglu, Hasan (Emerald Group Publishing Ltd, 2024)
Purpose This paper aims to investigate the effect of shear rate, concentration (4-20 kg/m(3)) and temperature (20 degrees C-60 degrees C) on the apparent viscosity of apricot gum solutions. Design/methodology/approach Apparent viscosity has been measured using a rotational viscometer. Findings It has been observed that the shear stress and apparent viscosity values increase at high concentrations in the prepared apricot gum solutions. However, it is understood that the higher the temperature in the operation conditions, the lower the apparent viscosity results. Power-law is found the best-fitting model to illustrate the changes in temperature and concentration. According to the consistency coefficient and flow behavior indices, the apricot gum displayed shear-thinning behavior (pseudoplastic). The apricot gum is a polysaccharide with amino and uronic acids, according to Fouirer Transform Infrared Spektrofotometre spectra. Practical implications The results suggest that power-law model can be used to estimate the viscosity of apricot gum solutions at different temperatures and concentrations for applications for which flow behavior should be taken into account. Originality/value Exudate gums have good rheological properties and, therefore, are widely used in the food industry. Apricot gum is a biodegradable and abundant polysaccharide that enhances viscosity, stabilizes suspension or emulsion and improves the flow properties of foods. Different rheological models are used to investigate rheological properties. However, those models are time-independent to fit the experimental data.
Keywords: Apricot gum; Rheology; Pseudoplastic; Power-law model; Statistical analysis